The Analysis of Dyscalculia Students Learning Difficulty in Inclusive Education of Primary School Level in Tasikmalaya - Nani Ratnaningsih; Ebih A R Arhasy; Edi Hidayat (STKIP Singkawang, 2019)
Inclusive education is a government program that is realized through an inclusive school program to help students with disabilities so that their formal education can be well served. The implementation of inclusive education in Tasikmalaya City and District is less encouraging, various plans for implementing inclusive education need to be taken seriously. The purpose of this study: studying, analyzing, and describing the learning difficulties of dyscalculia students; discuss the challenges or learning process in inclusive schools for dyscalculia students. The method used in this study is descriptive qualitative and think aloud was carried out at 4 inclusive schools in Tasikmalaya namely SDN Manggungjaya 1, SDN Sukasirna, SDN Cibungkul and SDN Tanjung 2. The subjects in this study were principals, class teachers in inclusive schools, and dyscalculia students in grades 4, 5 and 6 of each. The methods used in this study were descriptive qualitative and think aloud. The instruments used the researchers themselves and questionnaires. The data were collected using observation, exploration, and interviews, all data obtained analyzed then described narratively. Based on the results of data analysis concluded: dyscalculia students in grades 4, 5 and 6 still have difficulty in reading and counting operations in numbers up to 50, do not understand negative integers. Just learning to study is still very difficult to condition, teachers who often teach dyscalculia students with their own learning styles. Learning is still held by the class teacher when the teacher comes from the Special Needs School. Ideally, at least two students with disabilities, provided by teachers who have a special education background.